Modulation of electrical performance of zigzag edged tetra-penta-octagonal graphene nanoribbons based devices via boundary passivations - Kangwei Cen (Elsevier, 2021)
Recently, an sp2hybridized planar two-dimensional graphene-based carbon allotrope composed of tetra-penta-octagonal rings has attracted considerable interest. The electronic structures and transport properties of zigzag-edged tetra-penta-octagonal-graphene nanoribbons (TPO-ZGNRs) modified via boundary passivation were investigated using density functional theory and the non-equilibrium Green’s function. TPO-ZGNRs were passivated with H, 2H, O, OH, and Cl on the edge to produce TPO-ZGNRs-X (X=H, 2H, O, OH, and Cl). TPO-ZGNRs-H exhibits metallic properties regardless of the nanoribbon width and exists in the non-magnetic state. Although TPO-ZGNRs-OH and TPO-ZGNRs-Cl remain metallic, TPO-ZGNRs-2H and TPO-ZGNRs-O are semiconductors. In addition, the current–voltage curves of three TPO-ZGNRs-X (X=H, OH, and Cl) homojunction device models contain a negative differential resistance region. Notably, the heterojunction device model in which TPO-ZGNRs are passivated with H and O atoms at different edge regions has negative differential resistance and rectification characteristics. This study is expected to facilitate the development of new carbon materials.